North America and South America (NA-SA) neuropathy project. (1st August 2013) - Pasnoor, Mamatha; Nascimento, Osvaldo J. M.; Trivedi, Jaya; Wolfe, Gil I.; Nations, Sharon; Herbelin, Laura; de Freitas, M. G.; Quintanilha, Giseli; Khan, Saud; Dimachkie, Mazen; Barohn, Richard
Abstract : Peripheral neuropathy is a common neurological disorder. There may be important differences and similarities in the diagnosis of peripheral neuropathy between North America (NA) and South America (SA). Neuromuscular databases were searched for neuropathy diagnosis at two North American sites, University of Kansas Medical Center and University of Texas Southwestern Medical Center, and one South American site, Federal Fluminense University in Brazil. All patients were included into one of the six major categories: immune-mediated, diabetic, hereditary, infectious/inflammatory, systemic/metabolic/toxic (not diabetic) and cryptogenic. A comparison of the number of patients in each category was made between North America and South America databases. Total number of cases in North America was 1090 and in South America was 1034 [immune-mediated: NA 215 (19.7%), SA 191 (18%); diabetic: NA 148 (13.5%), SA 236 (23%); hereditary: NA 292 (26.7%), SA 103 (10%); infectious/inflammatory: NA 53 (4.8%), SA 141 (14%); systemic/metabolic/toxic: NA 71 (6.5%), SA 124 (12%); cryptogenic: NA 311 (28.5%), SA 239 (23%)]. Some specific neuropathy comparisons were hereditary neuropathies [Charcot–Marie–Tooth (CMT) cases] in NA 246/292 (84.2%) and SA 60/103 (58%); familial amyloid neuropathy in SA 31/103 (30%) and none in NA. Among infectious neuropathies, cases of human T-lymphotropic virus type 1 (HTLV-1) neuropathy in SA were 36/141(25%), Chagas disease in SA were 13/141(9%) and none for either in NA; cases of neuropathy due to leprosy in NA were 26/53 (49%) and in SA were 39/141(28%). South American tertiary care centers are more likely to see patients with infectious, diabetic and hereditary disorders such as familial amyloid neuropathies. North American tertiary centers are more likely to see patients with CMT. Immune neuropathies and cryptogenic neuropathies were seen equally in North America and South America.